Two possible improvements for mass spectrometry analysis of intact biomolecules. Issue 4 (August 2017) - Raznikov, Valeriy V; Zelenov, Vladislav V; Aparina, Elena V; Pikhtelev, Alexander R; Sulimenkov, Ilia V; Raznikova, Marina O
The goals of our study were to investigate abilities of two approaches to eliminate possible errors in electrospray mass spectrometry measurements of biomolecules. Passing of a relatively dense supersonic gas jet through ionization region followed by its hitting the spray of the analyzed solution in low vacuum may be effective to keep an initial biomolecule structure in solution. Provided that retention of charge carriers for some sites in the biomolecule cannot be changed noticeably in electrospray ion source, decomposition and separation of charge-state distributions of electrosprayed ions may give additional information about native structure of biomolecules in solution.